The Effect of Ozone Therapy on the Healing Process of Diabetic Mellitus Wounds at the DD Care Clinic of the Wound, Stoma and Continental Care Center, Padang City - Wenny Lazdia; Faridah Mohd Said; Nisha Nambiar; Evi Hasnita (Al Makki Publisher, 2024)
Diabetes mellitus (DM) is a chronic disease that can cause various complications, including diabetic foot wounds. Wound healing in diabetic patients is often hampered, so effective therapy is needed. Ozone therapy has shown potential in accelerating the wound healing process through increased tissue oxygenation and antimicrobial effects. This study aims to determine the effect of ozone therapy on the wound healing process of diabetes mellitus at DD Care Clinic Padang City. This study used a quasi-experimental design with a one group pretestposttest method. A sample of 10 people was taken with purposive sampling technique. Data were collected using the Bates-Jensena Wound Assessment Tool (BWAT) questionnaire and analyzed using the Wilcoxson signed ranks test. The mean diabetic wound healing score before ozone therapy was 41.1 (SD 7.34) and after therapy was 25.3 (SD 7.39). The statistical test showed a P value of 0.005, which indicated a significant difference between the scores before and after therapy. The results showed that ozone therapy is effective in accelerating diabetic wound healing. This therapy works by increasing oxygenation, reducing infection, and stimulating cell regeneration. This finding is in line with previous studies that show the benefits of ozone in wound management. There is a significant effect of ozone therapy on the wound healing process of diabetes mellitus at DD Care Clinic, with a P-value of 0.005. Therefore, it is recommended that healthcare professionals consider using ozone therapy in diabetic wound care protocols to improve clinical outcomes.